Placement of a peripherally inserted central catheter into the azygous vein. Issue 2 (18th February 2015) - Franklin, Iain; Gilmore, Christopher
Abstract Peripherally inserted central catheters (PICC) are used for a variety of infusion therapies. They are indicated in patients requiring long‐term venous access. Incorrect positioning of the insertion of a PICC line is one of the known complications when inserting the device in clinical practice. Radiographers once performing imaging will commonly check if the tip of a PICC has entered the superior vena cava. This case study will report on a lesser known incorrect placement of a PICC line into the azygous vein and how this can be detected on radiographic imaging. This outcome for the patient can be detrimental as it has an increased risk of perforation, thrombus, and fistula formation.